Influence of Lithium ions on conidiophore size in Neurospora crassa - Bodil Aase; Ingunn W. Jolma; Peter Ruoff (Fungal Genetics Reports, 2006)
Lithium (Li) ions are known to affect Neurospora crassa’s growth speed and circadian clock period, while elevated temperatures abolish these influences. We wondered whether Li has also an effect on conidia size. We used cryo-SEM to investigate this question and report here the results of 1720 measurements showing that at 20°C the long and short conidial axes are significantly reduced at high Li concentrations (10-15 mM), while the ratio between the long and short axes remains approximately constant. An increased temperature (30°C) appears to abolish the Li effect on conidia size.